Faktor-Faktor yang Berhubungan dengan Kejadian Karies Gigi pada Anak - Eny Pemilu Kusparlina (FORUM ILMIAH KESEHATAN, 2020)
Dental caries is a dental health problems that tend to be interpreted as cavities, where as teeth with white spots or brown can be said to have caries. Dental caries affects many children because the children do not understand the importance of maintaining healthy teeth. The purpose of this study was to identify factors associated with the incidence of dental caries in children in kindergarten Al Hidayah I Manisrejo village. This type of research is descriptive and correlation with cross-sectional design approach. The population is a kindergarten student and the student's mother Al Hidayah I Manisrejo A group numbering 37 pairs of mothers and children. Sampling technique using total sampling as many as 37 pairs. Using descriptive analysis and bivariate frequency distributions using chi square. The results showed that students with family socio economic level quite as many as 15 respondents (42.9%), mother's education level students with basic education by 30 respondents (85.7%), students with high levels of cariogenic food consumption by 28 respondents (80 %), students with poor brushing habits by 30 respondents (85.7%), and students who suffer from dental caries by 30 respondents (85.7%). There is a significant relationship between socio-economic level of families with children the incidence of dental caries (X2 11 181, p 0.004), a significant correlation between the level of maternal education with incidence of dental caries children (X2 20 572, p 0.001), a significant correlation between the level of consumption cariogenic diet with the incidence of dental caries (X2 23 333, p 0.001), and there is a relationship between tooth brushing habits with incidence of dental caries (X2 35.000, p 0.001). Keywords: caries; socio economic; education; cariogenic foods; brushing habits ABSTRAK Karies gigi merupakan masalah kesehatan gigi yang cenderung diinterpretasikan sebagai gigi berlubang, padahal gigi dengan bercak putih atau coklat pun bisa disebut menderita karies. Karies gigi banyak diderita oleh anak -anak dikarenakan anak -anak belum memahami pentingnya menjaga kesehatan gigi. Tujuan penelitian ini untuk mengidentifikasi faktor -faktor yang berhubungan dengan kejadian karies gigi pada anak di TK Al Hidayah I Manisrejo. Jenis penelitian adalah observasional dengan desain pendekatan Cross Sectional. Populasinya adalah siswa dan ibu siswa TK Al Hidayah I Manisrejo kelompok A berjumlah 37 pasang ibu dan anak. Teknik sampling menggunakan total sampling yaitu sebanyak 37 pasang. Analisis deskriptif menggunakan distribusi frekuensi dan bivariat menggunakan chi square. Hasil penelitian menunjukkan bahwa siswa dengan tingkat sosial ekonomi keluarga cukup sebanyak 15 responden (42,9%), siswa dengan tingkat pendidikan ibu pendidikan dasar sebanyak 30 responden (85,7%), siswa dengan tingkat konsumsi makanan kariogenik tinggi sebanyak 28 responden (80%), siswa dengan kebiasaan menyikat gigi buruk sebanyak 30 responden (85,7%), dan siswa yang menderita karies gigi sebanyak 30 responden (85,7%). Terdapat hubungan yang signifikan antara tingkat sosial ekonomi keluarga dengan kejadian karies gigi anak (X2 11.181, p 0,004), terdapat hubungan yang signifikan antara tingkat pendidikan ibu dengan kejadian karies gigi anak (X2 20.572, p 0,001), terdapat hubungan yang signifikan antara tingkat konsumsi makanan kariogenik dengan kejadian karies gigi (X2 23.333, p 0,001) dan terdapat hubungan yang signifikan antara kebiasaan menyikat gigi dengan kejadian karies gigi (X2 35.000, p 0,001). Kata kunci: karies; sosial ekonomi; pendidikan; makanan kariogenik; menyikat gigi